1981
DOI: 10.1258/002367781780958919
|View full text |Cite
|
Sign up to set email alerts
|

Metomidate, etomidate and fentanyl as injectable anaesthetic agents in mice

Abstract: Light surgical anaesthesia lasting 12-15 min was produced by metomidate at 50 mg/kg and by etomidate at 30 mg/kg after intraperitoneal injection. Full surgical anaesthesia lasting about 160 min was achieved after subcutaneous injection of a metomidate-fentanyl mixture (60 mg/kg:0·06 mg/kg) and this proved superior to etomidate-fentanyl given subcutaneously or intraperitoneally. It was concluded that metomidate-fentanyl is superior to pentobarbitone and tribromoethanol as an injectable anaesthetic for mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As indicated in available literature, etomidate is administered to mice at doses ranging from 0.3 to 30 mg•kg -1 (22)(23)(24). Studies have shown that the sleep duration in mice injected with etomidate is dose-dependent but can last for 6-10 min at 0.3 mg•kg -1 , and recovery is rapid and complete without any signs of hangover (25). Therefore, 0.3 mg•kg -1 was selected as the minimum dose.…”
Section: Low and Moderate Doses Of Etomidate Decreases The Lung W/dmentioning
confidence: 99%
“…As indicated in available literature, etomidate is administered to mice at doses ranging from 0.3 to 30 mg•kg -1 (22)(23)(24). Studies have shown that the sleep duration in mice injected with etomidate is dose-dependent but can last for 6-10 min at 0.3 mg•kg -1 , and recovery is rapid and complete without any signs of hangover (25). Therefore, 0.3 mg•kg -1 was selected as the minimum dose.…”
Section: Low and Moderate Doses Of Etomidate Decreases The Lung W/dmentioning
confidence: 99%
“…Henke et al [8] recently advocated the use of MCF because it leads to fewer cardiovascular and respiratory side effects and especially because it has the advantage of reversibility. MCF has also been known for decades [7], but has only been used rarely, according to the literature. Metabolic acidosis has so far not been reported for MCF anesthesia in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, KX has the disadvantage that it depresses the cardiovascular and respiratory systems of various animals [3][4][5][6]. Other combinations of narcotics, such as medetomidine/climazolam/fentanyl (MCF) [7,8], have been reported to cause less unpleasant side effects, and were regularly recommended in the past. The ability to reverse the effects of each drug separately is especially appealing.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine has proved a valuable CNS depressant in the management of small animals in that it is effective Ketamine-acepromazine anaesthesia in chinchillas when injected im and has a wide margin of safety, but it is far more useful if given with agents having central muscular relaxant properties such as diazepam or xylazine (Green, 1979;Green, Knight, Precious & Simpkin, 1981). We have found it, in conjunction with acepromazine, to be effective for surgical anaesthesia in chinchillas.…”
Section: Discussionmentioning
confidence: 99%